2016
DOI: 10.1002/hbm.23129
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in amygdala–frontal connectivity during emotional face processing from childhood into young adulthood

Abstract: The ability to process and respond to emotional facial expressions is a critical skill for healthy social and emotional development. There has been growing interest in understanding the neural circuitry underlying development of emotional processing, with previous research implicating functional connectivity between amygdala and frontal regions. However, existing work has focused on threatening emotional faces, raising questions regarding the extent to which these developmental patterns are specific to threat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
108
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(122 citation statements)
references
References 75 publications
(103 reference statements)
13
108
1
Order By: Relevance
“…In the present sample of healthy subjects, increased GP and PUT reactivity towards negative faces was found to be positively associated with both depression and social anxiety symptoms. This is consistent with previous meta-analyses on depression and social anxiety disorders showing increased reactivity in these regions during emotional face processing (Binelli et al, 2014;Delvecchio et al, 2012;Gee et al, 2013;Kanske and Kotz, 2011a,b;MacQueen, 2012;Wu et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present sample of healthy subjects, increased GP and PUT reactivity towards negative faces was found to be positively associated with both depression and social anxiety symptoms. This is consistent with previous meta-analyses on depression and social anxiety disorders showing increased reactivity in these regions during emotional face processing (Binelli et al, 2014;Delvecchio et al, 2012;Gee et al, 2013;Kanske and Kotz, 2011a,b;MacQueen, 2012;Wu et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…In the present sample of healthy subjects, increased GP and PUT reactivity towards negative faces was found to be positively associated with both depression and social anxiety symptoms. This is consistent with previous meta‐analyses on depression and social anxiety disorders showing increased reactivity in these regions during emotional face processing (Binelli et al, ; Delvecchio et al, ; Gee et al, ; Kanske and Kotz, ; MacQueen, ; Wu et al, ). As core regions of the dorsal striatum and the basal ganglia, both GP and PUT, are not only involved in motor functions, but also play important roles in other domains, such as emotional regulation (Frank et al, ; Sztainberg, Kuperman, Justice, & Chen, ), salience processing (Gentili et al, ; Menon, ; Smith, Berridge, & Aldridge, ) and social‐cognitive functions (MacQueen, ).…”
Section: Discussionsupporting
confidence: 91%
“…Adult participants and parents of children under the age of 18 provided written informed consent and verbal assent was obtained from minors. We previously reported on typical age-related changes in brain activation and amygdala connectivity during emotional face processing in this sample of healthy volunteers (23) and on neural processing of emotional faces in separate studies of anxious youth (18) and young adults (24; 25). In this paper, we extend this work by combining pediatric and adult samples to examine age-related changes in amygdala connectivity in anxiety.…”
Section: Methodsmentioning
confidence: 95%
“…Unlike in the adult, these regulatory influences from the medial PFC are not available to the young child. Several studies have now shown that functional connections between the amygdala and the medial PFC are immature in childhood[30, 32, 55]and switch to the adult-like state in adolescence (Fig 2, bottom)[29, 5659]. That is, during childhood the amygdala is less likely to be regulated by the mPFC than after childhood.…”
Section: The Amygdala As a Studentmentioning
confidence: 99%